A Prototype Development of an Autonomous Robot for the Inspection of Suspension Spring Profiles in Toyota Hilux Pickups - Godiel, Jorge (2024)
Companies engaged in mining vehicle rental face challenges in adequately inspecting the condition of suspension springs due to time constraints. To address this issue and monitor the suspension of Toyota Hilux trucks before and after rental service, we propose a prototype development of an autonomous robot. The robot utilizes a SLAM-based navigation system to reach specified positions, while a robot arm control system positions a camera for inspecting spring suspension profiles. We studied the vehicle and robot arm position control systems, conducted dynamic simulations of the robot arm, designed the robot system architecture using ROS, simulated the robot using ROS Gazebo, and developed an algorithm to generate a technical inspection report with registered spring photographs. Navigation is facilitated by an A1M8 Lidar sensor. Data processing is performed using a Raspberry Pi 4B 8 GB with ROS. Image analysis will be developed in future work. The proposed approach’s effectiveness will be validated through autonomous mapping and navigation in three distinct work areas. The main contribution of this work is the development of an autonomous robot programmed in ROS Noetic that monitors the suspension spring profiles of Toyota Hilux trucks during their service life by acquiring photographs of the suspension elements.